Detection of Enterobacteriaceae Lactose Fermenter Bacteria Producing Extended Spectrum Beta-Lactamase (ESBL) in Food Samples at Surabaya - Parawidnyaningsih, Putu Ayu Aryanda; masfufatun, masfufatun; Listyawati, Agusniar Furkani; Kuntaman, Kuntaman; Sudibya, Akhmad (Bioma : Jurnal Ilmiah Biologi, 2023)
Snacks sold on the side of the road are often purchased because they are practical and cheap. The condition of food sold in the open causes a decrease in food hygiene, so bacteria will easily contaminate, both due to flies infesting it and direct contact with the hands of people around it. One group of bacteria that can cause infection and often contaminate food is Enterobacteriaceae. These bacteria can produce Extended Spectrum Beta Lactamase (ESBL) enzymes that cause resistance to various antibiotics (MDR). This research aims to detecting ESBL-producing Enterobacteriaceae lactose fermenter bacteria in street food sold on the side of the road in the Dukuh Kupang market area, Surabaya. This study is descriptive observational research with a cross-sectional research design. A total of 50 snack food samples were grown on MacConkey agar containing cefotaxime at four micrograms per milliliter. Then an ESBL confirmation test was carried out using the double disk synergy test (DDST). The Result showed that 13 (26%) samples of snack foods were contaminated. ESBL-producing Enterobacteriaceae Lactose Fermenter bacteria are ubiquitous. The most contaminated snack food was cassava, while the non-contaminated snack food was stuffed tofu.